SURVEI ATTITUDE DAN MOTIVASI PADA ATLET ASJAD BADMINTON CLUB - Suhardimansyah, Muhammad Riedho; Rubiyatno, Rubiyatno; Perdana, Rahmat Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine and analyze the attitudes and motivations of ASJAD Badminton Club athletes. This study uses a survey method with a quantitative descriptive approach, where data is collected through a questionnaire distributed to 20 ASJAD Badminton Club athletes. The questionnaire used consists of items related to attitudes towards training, competition, and coaches, as well as intrinsic and extrinsic motivation in achieving. The results of the study showed that in the attitude category, 6 athletes received a score of "Very Good" with a percentage of 30%, 14 athletes received a score of "Good" with a percentage of 70% of the total sample percentage of 100%, none received a score of "Enough", "Less", and "Very Less". In the motivation category, there were 7 athletes who were included in the "Very Good" category with a percentage of 35%, while 13 athletes were included in the "Good" category with a percentage of 65% of the total sample 100%, none received a score of "Enough", "Less", and "Very Less".